2010
DOI: 10.21273/hortsci.45.4.693
|View full text |Cite
|
Sign up to set email alerts
|

Bermudagrass Reseeding Intervals for Rimsulfuron, Simazine, and Sulfosulfuron

Abstract: Turf managers may wish to reseed common bermudagrass [Cynodon dactylon (L.) Pers.] following weed control with rimsulfuron, simazine, or sulfosulfuron applications, but establishment may be affected by herbicide residual activity. Field experiments were conducted in Georgia to investigate bermudagrass reseeding intervals for these herbicides. Application timing before seeding reduced bermudagrass establishment more than herbicide rate. By four weeks after seeding, bermudagras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In analytical studies, metsulfuron and chlorsulfuron hydrolysis at pH 7 and 10 was slow (Berger and Wolfe 1996). Although this can be good for weed control, it can lead to increased injury to somewhat sensitive turfgrass species when trying to reestablish turf by seed (Lycan and Hart 2005;McCullough and Nutt 2010). Chemical degradation tends to be temperature-dependent for SUs with half-life (DT 50 ) decreasing with increasing temperature (Sarmah and Babadie 2002).…”
Section: Chemical Degradationmentioning
confidence: 99%
“…In analytical studies, metsulfuron and chlorsulfuron hydrolysis at pH 7 and 10 was slow (Berger and Wolfe 1996). Although this can be good for weed control, it can lead to increased injury to somewhat sensitive turfgrass species when trying to reestablish turf by seed (Lycan and Hart 2005;McCullough and Nutt 2010). Chemical degradation tends to be temperature-dependent for SUs with half-life (DT 50 ) decreasing with increasing temperature (Sarmah and Babadie 2002).…”
Section: Chemical Degradationmentioning
confidence: 99%
“…However, these grasses were safely established when bispyribac sodium was applied 2 WBS (Lycan and Hart, 2006). Sulfosulfuron at 13 to 26 g/a.i./ha applied the day of seeding or 1 WBS reduced creeping bentgrass and kentucky bluegrass establishment compared with the non-treated control (McCullough and Nutt, 2010;Willis et al, 2007). Amicarbazone applied at 0.4 kgÁha -1 has the potential to reduce perennial ryegrass and tall fescue cover when applied the day of seeding.…”
mentioning
confidence: 99%
“…Common bermudagrass [Cynodon dactylon (L.) Pers.] seedlings have shown significant injury and reduced establishment in response to rimsulfuron, simazine, and trifloxysulfuron applied 1 to 2 WBS (McCullough and Nutt, 2010;Willis et al, 2007). McCalla et al (2004) reported that 'Princess 77' bermudagrass seedlings exhibited 30% or less injury after applications of diclofop, metsulfuron, 2,4-D, dicamba, monosodium acid methanearsonate (MSMA), clopyralid, and quinclorac applied 1, 2, and 4 weeks after emergence.…”
mentioning
confidence: 99%
“…Lycan and Hart (2006b) noted reductions in creeping bentgrass, kentucky bluegrass (Poa pratensis L.), and perennial ryegrass seedling cover from bispyribac-sodium applied 1 week before seeding (WBS), but these grasses were safely established when herbicides were applied 2 WBS. Common bermudagrass (Cynodon dactylon L.) seedlings have shown significant injury and reduced establishment from rimsulfuron, simazine, and trifloxysulfuron applied 1 to 2 WBS (McCullough and Nutt, 2010;Willis et al, 2007). Furthermore, researchers noted sulfosulfuron at 13 to 26 g/a.i./ha applied the day of seeding or 1 WBS significantly reduced creeping bentgrass and kentucky bluegrass establishment from the untreated.…”
mentioning
confidence: 99%